A Analysis Of Information Technology Governance In Department of Communication And Informatics of Salatiga Using COBIT 5 Framework DSS Domain - Ratna Damayanti; Augie David Manuputty (Universitas Bina Darma, 2019)
Technological advances and strategic environmental changes encourage the government sector to improve bureaucratic performance and services. Salatiga's Department of Communication and Informatics (Diskominfo Kota Salatiga) is a service that provides communication and informatics, statistics and coding services. However, in carrying out their duties and functions, there are still problems which indicate that the IT governance process is still not optimal, so that there is a need for identification and assessment efforts. This study aims to analyze the maturity level of IT governance using the COBIT 5 framework domain Deliver, Service and Support (DSS). The results of this study indicate that the level of capability of the DSS01, DSS03 and DSS06 processes is at level 2 (Managed process). While the DSS02 and DSS04 processes are at level 1 (Performed process). The recommendations in each process may be an input for Diskominfo in improving the quality of public services and for realizing good governance.